Forage Radish Cover Crop Suppresses Winter Annual Weeds in Fall and Before Corn Planting - Lawley, Yvonne E; Weil, Ray R; Teasdale, John R (Agronomy journal, 2011)
Forage radish (Raphanus sativus L. var. longipinnatus) is a new winter cover crop in the Mid-Atlantic region. The objective of this project was to characterize the repeatability, amount, and duration of weed suppression during and after a fall-planted forage radish cover crop and to quantify the subsequent effect on no-till seeded corn (Zea mays L.). Forage radish cover crops were grown in 10 site-years in the coastal plain of Maryland and followed by a corn crop in seven site-years. Forage radish was compared to rye (Secale cereale L.) and no cover crop treatments. Early and typical corn planting dates along with contrasting herbicide management strategies were compared over four site-years. Forage radish produced 3.9 to 6.6 micrograms ha-1 of shoot dry matter and 1.3 to 3.2 micrograms ha-1 of fleshy root dry matter when planted before 1 September. Forage radish did not reduce population or grain yield in subsequent corn crops. Forage radish provided complete suppression of winter annual weeds in fall and early spring but the suppression did not persist into the subsequent cropping season. When forage radish cover crops were used in place of preplant burndown herbicide treatments to control weeds in early planted corn, some weeds were present at the time of corn emergence but corn yields were not reduced as long as emerged weeds were controlled with a postemergence herbicide. Strategies to use the weed suppression of forage radish cover crops should focus on fall weed suppression and the early spring preplant window of weed control.